THE VIEW FROM THE EAST ON THE PROBLEM FIELD OF WESTERN LITERARY AND THEORETICAL STU - Olena A. Mashchenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The study aims to determine the status of modern theoretical literary debate within the context of scientific theorizing in China and Japan. Growing understanding of the crisis of Euro-Atlantic literary-theoretical thought in the first two decades of the 21st century took shape in the publication of works by venerable specialists in the field of literary studies devoted to the causes of its occurrence and the taxonomy of directions and theoretical tools to overcome it. What unites this whole corpus of extensive research is an indirect or direct recognition of the decline of productive literary theoretical research, which came after the literary theoretical breakthrough of the late 60s of the 20th century. At the same time, the refusal to recognize Western literature as a model, artistic and aesthetic norm caused the emergence of powerful voices of authors whose writings are not directly shaped by the Western literary canon. Simultaneously, the refusal to recognize Western literature as a model, artistic and aesthetic norm caused the emergence of powerful voices of writers whose work is not directly shaped by the Western literary canon. The polemic started with the postcolonial discourse regarding the epistemological perspectives of Western literary theory in a situation of clash with a non-Western literary text, which, at the turn of the 21st century, developed into a reflection of its ontological potential. Both intellectuals and artists of the age of Multiculturalism, who relied on the Poststructuralist “breakthrough to the transcendental” on the one hand and on the philosophical nature as well as poetics and aesthetics of art of the East on the other, demonstrated that a complex of issues related to the future existence of literary theory risen by the literature itself, is much more sophisticated. First of all, these processes are caused by the early formation of new future horizons of world literature, in which artists with Eastern artistic and aesthetic background and knowledge play a major role. Following the mastering of the Western literary and aesthetic canon – rather a long period when the writings of these authors were derived from the general paradigm of Western literature – the formation of a new literature takes place, protesting Bhabha’s idea of mimicry as a way of survival and adaptation of the colonized and demonstrating the non-Western canon as its artistic source. The era of posttheory should testify that the rumours of the “death of the theory” may be greatly exaggerated in case the overcoming crisis of theory, which is based on literary knowledge originating from the East.